Challenges of Internationalisation of Small and Medium Enterprises in Montenegro - JOVOVIĆ, Milorad; FEMIĆ-RADOSAVOVIĆ, Bojana; ĐURAŠKOVIĆ, Jovan (Journal of Advanced Research in Management; Vol 8 No 1 (2017): JARM Volume VIII Issue 1(15) Summer 2017, 2017)
The study examines the challenges of the process of internationalisation of SMEs in Montenegro. The empirical data are the result of research into the barriers that managers of small and medium-sized enterprises in Montenegro recognized in the process of internationalisation. The study that we are presenting in this paper has shown that aside from internal constraints and barriers, linked to skills, competences, finance and human resources, there exist the problems of lack of information about foreign markets and access to foreign markets. Considering this, we found that in order to contribute to the process of internationalisation, institutional support should be directed towards providing a better introduction to foreign markets, in terms of information and in terms of facilitating access to foreign markets, whether it is through contacts, legal and technical assistance or promotion. Our finding is that a special role in this process should belong to economic diplomacy. We found that the previously identified constraints in terms of resources and capabilities that weigh upon small and medium enterprises in Montenegro can be overcome if these companies increase their orientation towards partnership strategies in foreign market entry. Partnership strategies, based upon foreign market entry of multiple (two or more) partner companies, that are already present in the ICT sector, can be a good example for other sectors in Montenegro, including the food & wine production supply industry, tourism etc.